Search for heavy vector-like quarks coupling to light quarks in proton-proton collisions at √s=7 TeV with the ATLAS detector* - Aad, Georges; Anders, Christoph; Andrei, George Victor; Childers, J. Taylor; Dietzsch, Thorsten; Geweniger, Christoph; Hanke, Paul; Henke, Michael; Khomich, Andrei; Kluge, Eike-Erik; Kugel, Andreas; Lendermann, Victor; et al. (Physics letters, 2012)
This Letter presents a search for singly produced vector-like quarks, Q, coupling to light quarks, q. The search is sensitive to both charged current (CC) and neutral current (NC) processes, pp→Qq→Wqq′ and pp→Qq→Zqq′ with a leptonic decay of the vector gauge boson. In 1.04 fb−1 of data taken in 2011 by the ATLAS experiment at a center-of-mass energy s=7 TeV, no evidence of such heavy vector-like quarks is observed above the expected Standard Model background. Limits on the heavy vector-like quark production cross section times branching ratio as a function of mass mQ are obtained. For a coupling κqQ=v/mQ, where v is the Higgs vacuum expectation value, 95% C.L. lower limits on the mass of a vector-like quark are set at 900 GeV and 760 GeV from CC and NC processes, respectively.
ATLAS Collaboration: G. Aad, C.F. Anders, V. Andrei, J.T. Childers, Y. Davygora, T.A. Dietzsch, C. Geweniger, P. Hanke, M. Henke, A. Khomich, E.-E. Kluge, A. Kugel, V. Lendermann, R. Maenner, K. Meier, F. Mueller, S. Poddar, V. Radescu, S. Schaetzel, V. Scharf, A. Schöning, N. Schroer, H.-C. Schultz-Coulon, R. Stamen, M. Wessels [und weitere]
Gesehen am 30.11.2018